Limited evidence for differences in the home advantage between genders and age groups in Dutch elite field hockey - Quast, A. M.; Schüt, L.-M.; Hill, Y. (International Journal of Sport Psychology, 2025)
Research on the home advantage suggests that men typically benefit more from playing at home than women and that the home advantage increases with age. However, these studies are typically based on popular sports with high data availability like soccer and rarely include comprehensive data on women and underage athletes. Therefore, to address this gap, this study examined whether these patterns also hold for Dutch elite field hockey - a sport highly similar to soccer but rarely examined. We analyzed the number of points won and goals scored for a total of 6,880 games from five seasons of the highest league for the U14, U16, U18, and seniors played between 2018 and 2023. While we found evidence for the home advantage for both men and women, despite small effect sizes, there were no significant gender differences. However, the differences that approached significance favored the women at the U16 and U18 level. Additionally, we did not observe significant changes in the home advantage with increasing age. These findings suggest that sport-specific patterns exist for the home advantage with regards to gender difference and maturation effects.